Environmental and social consequences for moving beyond archaic legislation and policy: delay and disjoint in water governance, Malawi - Chunga, Brighton A.; Kusi-Appiah, Andy; Masangano, Clement; Mwamsamali, Oswald K. (IWA Publishing, 2022)
As in many sub-Saharan African countries with increasing demand for natural resources, how to move from archaic water legislation to new and up-to-date policies that cover both environmental and social consequences of water governance has become an issue. This study reviews Malawi’s current governance framework and recommends a framework that takes Malawi’s developmental needs into account. Our review of the state of water legislation shows that there is a lack of enforcement of the policies themselves and the public is not even aware of its existence. Lack of enforcement and public awareness have resulted in environmental degradation which is creating a lot of environmental problems for the citizens of Malawi. This work recommends future efforts in rationale evidence-based policy and legislation review that involves and is supported by multiple stakeholders. We also recommend the need for routine policy and legislation reviews in order to take advantage of cuttingedge solutions to water management issues. This will not only enhance general awareness of key environmental policies and legislation but benefit from coordinated efforts from various players to arrest the ongoing environmental degradation resulting from an incoherent policy and apathy from Malawians.